Bangladesh Governance in the Health Sector : A Systematic Literature Review - Rose, Jonathan (World Bank, Dhaka, 2015)
The purpose of this systematic review is to inform the World Bank, development partners and other stakeholders on the state of governance in the health sector of Bangladesh. With billions2 of Bangladeshi Taka invested in the government-run health sector every year, financed by domestic and international sources, there have been numerous efforts to better understand the governance challenges in the sector. This report reviews sixty such reports and studies written by NGOs, academics, government entities, research institutions, consultants and development partners, in the last fourteen years. However, translating that research into policy dialogue and improvement has been challenged due to poor knowledge management, a lack of a systematic approach to research (building on earlier studies findings), and limited efforts to place the work in the public domain and discourse. This paper takes a systematic approach to the literature review, bringing the key findings together and evaluating the weight of evidence on the governance problems in the sector, as well as the gaps that should be addressed by future research efforts. This review furthermore emphasizes the need to understand the factors, and political economy factors in particular, that explain the current state of affairs. The review is structured to systematically assess this literature, leading to several broad conclusions. First, it identifies the structure and method of the review and outlines the categorization of the governance issues reviewed, and provides a background to the health sector. It then methodically summarizes the relevant literature for each governance issue, highlighting the lessons and identifying the gaps and weaknesses. The review ends by highlighting these gaps in research, with a view to improve its scope and impact.